UPPER AIRWAY DIMENSIONS DURING SLEEP – AN INVESTIGATION OF THE CHANGES AND INFLUENCES ON SLEEP QUALITY - R.VENKAT.MDS.,; D.BALAKRISHNAN.MS (ENT)., DLO, PHD.,; M.VASANTHAKUMAR.MDS., (International Journal of Pharma and Bio Sciences, 2015)
Upper airway dimensions are considered to get altered during sleep, causing reduced sleep efficiency, but a definitive association is not affirmed. 3-dimensional imaging analysis of the upper airway (UA) during sleep and comparison between healthy individuals and subjects with mild obstructive sleep apnea (OSA) will give a clear picture of the association between UA and sleep efficiency. Such an analysis will also help in studying different levels of UA obstruction and categorizing mild OSA subjects. Methods: A case- control study was planned with sample of 80 subjects- 40 healthy individuals(Control group -Group A), 40 subjects with mild OSA(Group B). Preliminary questionnaire for sleep analysis, Final data collection sheet was recorded, cephalometric variables analyzed and Diagnostic Overnight Polysomnography done to confirm selection criteria. 3-dimensional Computed tomography(CT) was done to analyze UA dimensions with computer softwares. UA 3d reconstruction and physical models were obtained by rapid prototyping. Conclusions: 1)UA dimensions are significantly reduced during sleep in mild OSA than healthy subjects; 2)Mild OSA with Retro-palatal zone of narrowing had a larger distribution among the samples (63.3%) thereby indicating that Retro-palatal zone of narrowing is more common.